THE PRACTICE OF CITY RESIDENTS IN INFORMALITY RIVERBANKS WINONGO YOGYAKARTA CITY - Rosesynta Paramita; Ahmad Ramdhon (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The city is a network of human life which is characterized by a high population density with colorful heterogeneous socioeconomic strata and materialist. Cities in Indonesia is currently undergoing a fairly rapid growth rate. This makes more and more people are interested to move and settle in the city. The impact of the activity of the townspeople always affects the environment inside. The river is one of the influences of the ecological activity of the city. The banks of the river became the site of the settlement of the community we callcity-village. City-Village inhabited by natives or newcomers with limited conditions that do daily activities to maintain his presence in the city. This research aims to 1) Describes social conditions the city-village of Winongo riverbanks. 2) The physical condition of the environment Winongo riverbanks. 3) Describes the everyday practice of residents of the city on the Winongo River. In this study used the thought of Pierre Bourdieu's theory of capital.  This study uses qualitative methods, Descriptive approach to generate the information. The selected informer is the original city residents, expat residents and FKWA as the Winongo River Community. Data collection using in-depth interviews, observation, and documentation. The research results showed that: 1) City-Village of winongo riverbanks have dynamics over time. Changes in total population seriring just time to make settlements in the city is getting memeadat. The presence of many routine activities collectively used to tie the laces of city-village on the Winongo River. 2) The physical condition of the city-villages and river more start specially degraded river conditions began declining quality is due to receive waste from human activities. Waste into the Winongo probelm and there needs to be an awareness to preserve the Winongo. 3) Everyday lives practice showed that the city-village’s Winongo riverbanks most of all its citizens with low socio economic circles. The daily activities of the city-village of this town is a form of adaptation should be done to connect to live. The idea of Bourdieu about capital, proved to be the fifth capital used in the everyday life of the city-village in sustaining life. Reciprocal relationships, networks, norms and trust strengthen city residents living in activity and connect live.